Pengaruh Pendapatan, Citra Lembaga, Kualitas Pelayanan terhadap Minat Membayar Zakat Maal melalui LAZ-UQ Jombang - Aningsih, Indri (Jurnal Ekonomika dan Bisnis Islam, 2019)
The aim of this research is to know the effect of income, institutional image and service quality toward the interest of muzakki in paying zakat maal through LAZ Ummul Quro’ in Jombang. This research applies quantitative approach with method multiple regression analysis. This research engaged 67 respondents as the samples with Random Sampling technique. The result indicates that the income , institutional image and service quality partially affects the interest in paying zakat maal at LAZ-UQ Jombang. Then, on simultaneous testing (simultaneously) income, institutional image and service quality variables affect the interest in paying zakat maal at LAZ-UQ Jombang.